2019
DOI: 10.1097/pcc.0000000000001894
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Family Functioning on the Development of Posttraumatic Stress in Children and Their Parents Following Admission to the PICU*

Abstract: Objectives: To report the rate of acute stress and posttraumatic stress among children and parents following PICU admission and the relation between family function and posttraumatic stress. Design: Prospective, longitudinal, multi-informant observational study. Pediatric patients (n = 69) and parents were recruited in the ICU. They completed measures evaluating acute stress and posttraumatic stress during their hospitalization and at 3-month follow-up.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 30 publications
2
43
1
1
Order By: Relevance
“…Although the perceived stress symptoms overall did not significantly differ between the experimental and control groups as expected at T2 or T3, there was a significant relationship between experimental parents' perceived stress during the child's hospitalization in the PICU and their posttraumatic stress symptoms after discharge. This is consistent with recent research that showed parents acute stress during their child's hospitalization positively predicted parent's posttraumatic stress 3 months after discharge (Nelson et al, 2019). The small sample size of this feasibility and acceptability study was not adequately powered to detect a statistically significant difference between groups.…”
Section: Discussionsupporting
confidence: 92%
“…Although the perceived stress symptoms overall did not significantly differ between the experimental and control groups as expected at T2 or T3, there was a significant relationship between experimental parents' perceived stress during the child's hospitalization in the PICU and their posttraumatic stress symptoms after discharge. This is consistent with recent research that showed parents acute stress during their child's hospitalization positively predicted parent's posttraumatic stress 3 months after discharge (Nelson et al, 2019). The small sample size of this feasibility and acceptability study was not adequately powered to detect a statistically significant difference between groups.…”
Section: Discussionsupporting
confidence: 92%
“…PTSD is particularly common amongst critically ill children [ 70 ]. As many as 84.6% of PICU survivors compared to 6.2% of ward survivors met criteria for probable PTSD or actual Diagnosis and Statistics Manual of Mental Disorders 5th edition (DSM5) criteria, according to an Egyptian study [ 71 ], while other studies report that 13–32% of children screen positive for PTSD within a year of discharge [ 27 , 72 ]. PTSD symptoms are thought to improve over time [ 72 ].…”
Section: Emotional and Psychological Manifestationsmentioning
confidence: 99%
“…Parental psychological health is closely linked to their child’s psychosocial wellbeing and their ability to support their child’s recovery [ 72 , 75 ]. In total, 21% of parents experience moderate to severe anxiety, and 9% reported moderate–severe depression [ 84 ].…”
Section: Social Manifestations and Pics-familymentioning
confidence: 99%
“…Maternal education (16,64,65) and mental illness (16,66,67) have repeatedly been identified as risk factors for child development, in addition to low socioeconomic status (16,68,69) and social support (70,71). Cheung and colleagues report that up to 30% of families have at least one social determinant of health on admission to PICU, with half of these having multiple needs (72).…”
Section: Parent/family Factorsmentioning
confidence: 99%